Genetic assessment of environmental features that influence deer dispersal: implications for prion‐infected populations. Issue 2 (8th January 2014) - Kelly, Amy C.; Mateus‐Pinilla, Nohra E.; Brown, William; Ruiz, Marilyn O.; Douglas, Marlis R.; Douglas, Michael E.; Shelton, Paul; Beissel, Tom; Novakofski, Jan
Abstract: The landscape can influence host dispersal and density, which in turn, affect infectious disease transmission, spread, and persistence. Understanding how the landscape influences wildlife dispersal and pathogen epidemiology can enhance the efficacy of disease management in natural populations. We applied landscape genetics to examine relationships among landscape variables, dispersal of white‐tailed deer hosts and transmission/spread of chronic wasting disease (CWD), a fatal prion encephalopathy. Our focus was on quantifying movements and population structure of host deer in infected areas as a means of predicting the spread of this pathology and promoting its adaptive management. We analyzed microsatellite genotypes of CWD‐infected and uninfected deer from two disease foci (Southern Wisconsin, Northern Illinois). We quantified gene flow and population structure using F ST, assignment tests, and spatial autocorrelation analyses. Gene flow estimates were then contrasted against a suite of landscape variables that potentially mediate deer dispersal. Forest fragmentation and grassland connectivity promoted deer movements while rivers, agricultural fields and large urbanized areas impeded movement. Landscape variables, deer dispersal, and disease transmission covaried significantly and positively in our analyses. Habitats with elevated host gene flow supported the concept of dispersal‐mediated CWD transmission by reflecting a concomitant, rapid CWD expansion. Large, interrelated social groups isolated by movement barriers overlapped disease foci, suggesting that philopatry exacerbated CWD transmission. Our results promote adaptive management of CWD by predicting patterns of its spread and identifying habitats at risk for invasion. Further, our landscape genetics approach underscores the significance of topography and host behavior in wildlife disease transmission.